Impact of exercise training on physical and cognitive function among older adults: a systematic review and meta-analysis - Falck, Ryan S.; Davis, Jennifer C.; Best, John R.; Crockett, Rachel A.; Liu-Ambrose, Teresa (Neurobiology of aging, 2019)
Exercise plays a key role in healthy aging by promoting both physical and cognitive function. Physical function and cognitive function appear to be interrelated and may share common mechanisms. Thus, exercise-induced improvements in physical function and cognitive function may co-occur and be associated with each other. However, no systematic review has specifically assessed and compared the effects of exercise on both physical function and cognitive function in older adults, and the association between changes in both outcomes after exercise training. Thus, we conducted a systematic review and meta-analysis (N = 48 studies) among older adults (60+ years). These data suggest exercise training has a significant benefit for both physical function (g = 0.39; p < 0.001) and cognitive function (g = 0.24; p < 0.001). At the study level, there was a positive correlation between the size of the exercise-induced effect on physical function and on cognitive function (b = 0.41; p = 0.002). Our results indicate exercise improves both physical and cognitive function, reiterating the notion that exercise is a panacea for aging well. •Maintaining physical and cognitive function is critical for healthy aging.•Physical function and cognitive function are linked and share common mechanisms.•Exercise training improves physical function and cognitive function.•Exercise-induced improvements in physical and cognitive function are associated.